2020
DOI: 10.2147/eb.s229814
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retinal Nerve Fiber Layer Thickness and Total Macular Volume in Multiple Sclerosis Subtypes and Their Relationship with Severity of Disease, a Cross-Sectional Study</p>

Abstract: Background: Optic neuritis (ON) is an inflammatory demyelinating lesion in the optic nerve, which is strongly associated with multiple sclerosis (MS). Optical coherence tomography (OCT) is a noninvasive technique for the evaluation of the retinal layers. Our aim was to examine OCT metrics including retinal nerve fiber layer thickness (RNFLT), and total macular volume (TMV), in MS subtypes and their relationship with duration, first manifestation, and severity of disease. Material and Methods: In this cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…In a two-year follow-up study, Garcia-Martin et al [ 21 ] found that RNFL changes occurred at a similar rate in non-affected eyes with no evidence of ON. Eslami et al [ 22 ] found a significant inverse correlation between MS duration and RNFL thickness, regardless of the presence or absence of ON.…”
Section: Discussionmentioning
confidence: 99%
“…In a two-year follow-up study, Garcia-Martin et al [ 21 ] found that RNFL changes occurred at a similar rate in non-affected eyes with no evidence of ON. Eslami et al [ 22 ] found a significant inverse correlation between MS duration and RNFL thickness, regardless of the presence or absence of ON.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that OCT is an essential imaging method for monitoring neurodegenerative diseases and MS. It was found that peripapillary retinal nerve fiber layer (ppRNFL) and macular thickness were associated with disease severity, cognitive and physical dysfunction in patients with MS [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, many clinical studies have demonstrated the usefulness of assessing, by OCT, the retinal nerve fiber layer thickness (RNFL-T) and the total macular volume (TMV) in patients with MS, considering the reduction of these parameters as biomarkers of disease progression [18,[23][24][25][26][27]. Instead, in RR-MS patients treated with fingolimod, there are no long-term studies that analyze macular and RNFL changes and assess the effect of these retinal changes on VA, low-contrast letter acuity (LCLA) and VF.…”
Section: Introductionmentioning
confidence: 99%